Fatigue Reliability Assessment of Steel Member Using Probabilistic Stress-Life Method - Dae-Hung Kang; Changhwan Jang; Yeon-Soo Park; Suk-Yeol Han; Jin Ho Kim (Advances in Mechanical Engineering, 2012)
The fatigue reliability of a steel member in a bridge is estimated by using the probabilistic stress-life method. The stress history of a member is defined as the loading block when a truck passes over a bridge, and the stress range frequency distribution of the stress history is obtained by a stress range frequency analysis. A probabilistic method is applied to the stress range frequency distribution, and the parameters of the probability distribution for the stress range frequency distribution are used in a numerical simulation. To obtain the probability of failure of a member under a loading block, Monte Carlo simulation is performed in conjunction with Miner's rule, the modified Miner's rule, and Haibach's rule for fatigue damage evaluation. Through these analyses procedures, we obtain an evaluation method for fatigue reliability that can predict the block number of the failure load and residual fatigue life.